2013
DOI: 10.1523/jneurosci.2030-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in White Matter Diffusion Affect Sleep Oscillations

Abstract: The characteristic oscillations of the sleeping brain, spindles and slow waves, show trait-like, within-subject stability and a remarkable interindividual variability that correlates with functionally relevant measures such as memory performance and intelligence. Yet, the mechanisms underlying these interindividual differences are largely unknown. Spindles and slow waves are affected by the recent history of learning and neuronal activation, indicating sensitivity to changes in synaptic strength and thus to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
132
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 69 publications
10
132
2
Order By: Relevance
“…An intriguing explanation for the spatial variability in spindle frequency but not in these other characteristics might be related to the effect of natural resonance frequencies. These are thought to be dependent on the anatomical structure of the thalamocortical modules (Rosanova et al, 2009), in particular that of the white-matter tracts that have been shown to affect the characteristics of the sleep waves (Piantoni et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…An intriguing explanation for the spatial variability in spindle frequency but not in these other characteristics might be related to the effect of natural resonance frequencies. These are thought to be dependent on the anatomical structure of the thalamocortical modules (Rosanova et al, 2009), in particular that of the white-matter tracts that have been shown to affect the characteristics of the sleep waves (Piantoni et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In young adult humans and rodents, white matter integrity in fiber tracts that form cortico-thalamic loops is associated with the quantitative and qualitative expression of sleep spindles (Piantoni et al, 2013; Steriade et al, 1987). In agreement with these findings, preliminary human data indicate that age-related deterioration in white matter integrity within the body and splenium of the corpus callosum predicts the severity of impaired sleep spindle expression in older adults (Mander et al, 2016b).…”
Section: What Are the Neurobiological Mechanisms Of Age-related Sleepmentioning
confidence: 99%
“…We argue that although most cells in the body can presumably undergo rest relatively independently, neurons must rest together, owing to their extensive interconnectivity 50 . Thus, the only strategy to provide rest for an individual neuron in the neocortex is to synchronously reduce activity of the entire network that directly or indirectly projects to that neuron.…”
mentioning
confidence: 92%